TEACHERS’ RESISTANCE IN USING ENGLISH MONOLINGUAL INSTRUCTION IN SEKOLAH KAWASAN (RETAIN, 2015)
Abstract Sekolah Kawasan is new program of Surabaya Education Department as the exchange of RSBI program. One of its rules is the English teacher should use English monolingual instruction during teaching and learning activity. Nevertheless, most of English teachers in Sekolah Kawasan prefer using Bilingual instruction rather than using English monolingual instruction. It indicates that there are possibilities of resistance in using English monolingual instruction by English teachers in Sekolah Kawasan. Thus, this study was conducted in order to answer these questions; (1) Do the English teachers in one of Sekolah Kawasan resist using English monolingual instruction? (2) What are their reasons for resisting English monolingual instruction in the EFL learning? And (3) In what ways does their resistance of using English monolingual instruction affect students’ response to use English effectively in classroom? It is a qualitative research which involved three teachers and 117 students of SMAN 11 Surabaya. The data are taken by observations and interviews. The results show that the three teachers resisted in using English monolingual instruction. There were four reasons that were underlay their resistance in using English monolingual instruction include their beliefs to use first language, students’ condition, teacher’s fatigue, and lack of time. Meanwhile, there were two kinds of students’ responses in relation with the teachers’ language choice. They were verbal response and non-verbal response. Verbal response included Yes/No response, Bahasa Indonesia response, and English response. Meanwhile, non-verbal reactions included keeping silent, doing the teacher’s order, raising hand before asking question, and nodding heads. Key Words: Resistance, English Monolingual Instruction, Sekolah Kawasan Abstrak Sekolah Kawasan adalah program baru dari Dinas Pendidikan Kota Surabaya sebagai pengganti dari program RSBI. Salah satu peraturannya adalah guru Bahasa Inggris harus menggunakan instruksi Bahasa Inggris tunggal selama kegiatan belajar mengajar. Namun, kebanyakan dari guru Bahasa Inggris di Sekolah Kawasan lebih menggunakan Instruksi dalam dua bahasa daripada menggunakan instruksi Bahasa Inggris tunggal. Hal ini menunjukkan bahwa terdapat penolakan dalam penggunaan instruksi Bahasa Inggris tunggal oleh guru Bahasa Inggris di Sekolah Kawasan. Oleh karena itu, penelitian ini dilakukan untuk menjawab pertanyaan sebagai berikut: (1) Apakah guru Bahasa Inggris di salah satu Sekolah Kawasan menolak menggunakan instruksi Bahasa Inggris tunggal atau tidak? (2) Apakah alasan-alasan mereka dalam penolakan penggunaan Bahasa Inggris tunggal di dalam pembelajaran Bahasa Inggris sebagai bahasa asing? (3) Dalam hal apa penolakan mereka mempengaruhi respon siswa untuk menggunakan Bahasa Inggris secara komunikatif di dalam kelas? Penelitian ini adalah penelitian kualitatif yang melibatkan tiga guru Bahasa Inggris dan 117 siswa dari SMAN 11 Surabaya. Data diambil dari observasi dan wawancara. Hasil penelitian menunjukkan bahwa tiga guru tersebut menolak menggunakan instruksi Bahasa Inggris tunggal. Terdapat empat alasan yang meletarbelakangi penolakan mereka terhadap penggunaan instruksi Bahasa Inggris tunggal diantaranya kepercayaan mereka terhadap penggunaan bahasa asal, kondisi siswa, kelelahan guru, dan kekurangan waktu. Sementara itu, terdapat dua macam respon dari siswa yaitu respon lisan dan respon bukan lisan. Respon lisan termasuk respon iya/tidak, respon dalam Bahasa Indonesia, dan respon dalam Bahasa Inggris. Selain itu, respon bukan lisan diantaranya tetap diam, melakukan perintah guru, mengangkat tangan sebelum bertanya, dan menganggukan kepala. Kata kunci: Penolakan, Instruksi Bahasa Inggris Tunggal, Sekolah Kawasan